2018
DOI: 10.1021/acs.iecr.7b04178
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Bioresidue to Compatibilize Sodium Montmorillonite and Linear Low Density Polyethylene

Abstract: Despite the improved thermal stability and mechanical properties of polymer−clay nanocomposites compared to pure polymeric materials, creating nanocomposites with enhanced thermomechanical properties requires a good compatibility and dispersion of the clay within the polymeric matrix. This paper introduces a bioresidue extracted from waste biomass to modify montmorillonite clay to compatibilize it with linear low density polyethylene (LLDPE). The biomodified clay was compounded, melt blended, and injection mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 58 publications
1
8
0
Order By: Relevance
“…In addition, T3 presents three well-differentiated peaks at 2θ = 14.03, 19.83 and 61.9, which are typical of montmorillonite organoclay. These outcomes agree well with results previously reported in the literature [77,78,79,80,81].…”
Section: Resultssupporting
confidence: 93%
“…In addition, T3 presents three well-differentiated peaks at 2θ = 14.03, 19.83 and 61.9, which are typical of montmorillonite organoclay. These outcomes agree well with results previously reported in the literature [77,78,79,80,81].…”
Section: Resultssupporting
confidence: 93%
“…For neat MMT, characteristic peaks are observed at 2θ = 7.09 o and 2θ = 19.82 o . The peak at 2θ = 19.82 • is characteristic for nonbasal reflections, due to the layered structure [21]. In the samples with 3 wt% of MMT, it can be observed that the MMT characteristic peak shifts to lower angles if compared to the peak of the pristine organoclay (which was at 2θ = 7.09 • for neat MMT), suggesting intercalation of the polymer molecules into the galleries of the clay.…”
Section: Mechanical Propertiesmentioning
confidence: 94%
“…It has been documented that when the surface of montmorillonite clay is treated with a particular biomodifier, an organophilic environment is created around the clay that improves the hydrophobic nature of the polymer, causing the polymer to be adsorbed onto the clay. , In other words, molecules of the compatibilizer act as a bridge between the hydrophobic polymer and the hydrophilic clay (Figure ).…”
Section: Resultsmentioning
confidence: 99%